2009
DOI: 10.1111/j.1469-8986.2009.00820.x
|View full text |Cite
|
Sign up to set email alerts
|

A facial electromyographic investigation of affective contrast

Abstract: Affective contrast refers to the tendency for stimuli to be judged as less evocative when preceded by more evocative same-valence stimuli. The authors used facial electromyographic (EMG) activity over corrugator supercilii, which is inversely related to affective valence, to determine if context influences underlying affective reactions. In Experiment 1, moderately pleasant pictures elicited less activity over corrugator supercilii when they were embedded among mildly pleasant, as opposed to extremely pleasant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Additionally, these results point to the importance of more continuous assessment of emotion over time, with measures such as psychophysiological monitoring. In particular, recent evidence (Larsen & Norris, 2009; Schaefer et al, 2014) has suggested that deactivation of corrugator muscles (forehead muscles active during frowning), measured through facial electromyography (EMG), may be a highly reliable index of positive emotion valence. Given that experienced valence has been challenging to measure online, this finding provides a promising future methodology for ongoing assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these results point to the importance of more continuous assessment of emotion over time, with measures such as psychophysiological monitoring. In particular, recent evidence (Larsen & Norris, 2009; Schaefer et al, 2014) has suggested that deactivation of corrugator muscles (forehead muscles active during frowning), measured through facial electromyography (EMG), may be a highly reliable index of positive emotion valence. Given that experienced valence has been challenging to measure online, this finding provides a promising future methodology for ongoing assessment.…”
Section: Discussionmentioning
confidence: 99%
“…A related possibility, when comparing our passive-viewing results to Bradley et al’s (2008), is that our run included only positive and neutral images, whereas the Bradley protocol also used negative images. The inclusion of negative images may have created a context in which greater variation in the emotional valence elicited by stimuli is present (Larsen & Norris, 2009), which could amplify the differential response to positive images. Finally, as previously mentioned, the use of a mixed design combining sustained and transient manipulations of positive affect is relatively novel, and it is not yet clear this design can be successful in inducing both tonic and phasic positive affect.…”
Section: Discussionmentioning
confidence: 99%
“…We endeavoured to be more ecologically valid by including medium attractive faces, although predictions for these faces are less clear. For example, the ZM muscle is less responsive to smaller changes in valence (Larsen & Norris, 2009; Larsen et al, 2003) so we may only be able to observe a difference between groups of high and low attractive images (i.e., prototypical and non-prototypical; Winkielman et al, 2006). …”
Section: The Current Studymentioning
confidence: 91%
“…We checked for outliers using z-scored data and we removed them. We further made a square root transformation of the SC and EMG values in order to normalize their distributions (Larsen & Norris, 2009). …”
Section: Data Preparationmentioning
confidence: 99%